2014
DOI: 10.2105/ajph.2014.302042
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Gun Ownership and Stranger and Nonstranger Firearm Homicide Rates in the United States, 1981–2010

Abstract: Our findings challenge the argument that gun ownership deters violent crime, in particular, homicides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 47 publications
1
36
0
Order By: Relevance
“…Although relatively rare in the aggregate, violence stemming from handguns increases the likelihood that encounters will become lethal (Braga, 2012;DeLisi, Piquero, & Cardwell, 2014;Farrington, Loeber, Stallings, & Homish, 2012;Reich, Culross, & Behrman, 2002). As such, handgun carrying among adolescents is a serious public health concern (Blum, 2001;Fowler, Dahlberg, Haileyesus, & Annest, 2015;Muula, Rudatsikira, & Siziya, 2008;Siegel et al, 2014) and public policy issue (Barry et al, 2015;Braga, 2012;Cross & Pruitt, 2014;Kleck, 2005Kleck, , 2015Wintemute, 2015aWintemute, , 2015b.…”
Section: Introductionmentioning
confidence: 99%
“…Although relatively rare in the aggregate, violence stemming from handguns increases the likelihood that encounters will become lethal (Braga, 2012;DeLisi, Piquero, & Cardwell, 2014;Farrington, Loeber, Stallings, & Homish, 2012;Reich, Culross, & Behrman, 2002). As such, handgun carrying among adolescents is a serious public health concern (Blum, 2001;Fowler, Dahlberg, Haileyesus, & Annest, 2015;Muula, Rudatsikira, & Siziya, 2008;Siegel et al, 2014) and public policy issue (Barry et al, 2015;Braga, 2012;Cross & Pruitt, 2014;Kleck, 2005Kleck, , 2015Wintemute, 2015aWintemute, , 2015b.…”
Section: Introductionmentioning
confidence: 99%
“…Siegel et al. () replicated this finding in their study of the homicides conducted in the United States between 1980 and 2008 of which the relationship between victim and offender was known (approximately 60% of all homicides). They reported that only one fifth of all homicides were stranger homicides.…”
Section: Guns and Homicide: Empirical Evidencementioning
confidence: 86%
“…Therefore, if guns were effective means of defending oneself against homicide attempts, higher gun ownership rates should be associated with lower rates of homicides committed by persons unknown to the victim (stranger homicides). To test this prediction, Siegel and colleagues () assessed the association between gun ownership rates in the 50 U.S. States between 1980 and 2008 (using the same gun ownership proxy as in the earlier study of Siegel et al., ). They found that gun ownership rates were unrelated to rates of stranger homicides but positively associated with nonstranger homicides.…”
Section: Guns and Homicide: Empirical Evidencementioning
confidence: 99%
“…A total of 32,888 individuals lost their lives due to firearms in 2013 with an additional 84,258 individuals experiencing non-fatal firearm related injuries (2, 3). Possessing a firearm is associated with an increased risk of being murdered or assaulted with a firearm as opposed to offering protection (4, 5). Firearms also play a significant role in suicide risk as a highly lethal means of suicide when available to many individuals who experience passing or impulsive suicidal thoughts (6).…”
Section: Introductionmentioning
confidence: 99%